(untitled) (International Journal of Plant Biology, 2017)
This study evaluates the antioxidant potential and free radical scavenging ability of whole grain finger millet. The crude extracts were obtained by cold maceration using 80% ethanol and methanol. Concentrated extracts were subjected to radicals of 2,2’-diphenyl-1-picrylhydrazyl hydrate (DPPH), hydrogen peroxide, nitric oxide (NO) and malondialdehyde, while the antioxidant constituents evaluated includes total phenol and flavonoid. The results revealed that whole grain finger millet contained 14.65±0.41 and 38.19±0.60 mg QUE/g sample of flavoniods, 36.46±1.09 and 67.10±1.17 mg GAE/g sample of total phenolics and 17.61±0.70 and 35.89±1.32 mg AAE/g sample of total antioxidant capacity for methanol and ethanol respectively. Ethanolic extract of whole finger millet scavenged above 50% hyrogen peroxide, NO and DPPH radicals. Hence, it terminated up to 8.97-65.16% lipid peroxidation reaction chain that may result from auto-oxidation, photo-oxidation and any other oxidation stress that may occur in plant and animal tissues. Therefore, pharmocology attention has to be given to finger millet which showed an effective antioxdants and antiradical capacities. Also, cultivation of finger millet should be encouraged by farmers.